A new silver nanochain SERS analytical platform to detect trace hexametaphosphate with a rhodamine S molecular probe. (17th August 2015) - Shang, Guangyun; Li, Chongning; Wen, Guiqing; Zhang, Xinghui; Liang, Aihui; Jiang, Zhiliang
Abstract: Using AgNO3 as the precursor, stable silver nanochain (AgNC) sols, orange‐red in color, were prepared using hydrazine hydrate. A strong surface plasmon resonance Rayleigh scattering (RRS) peak occurred at 420 nm plus two surface plasmon resonance (SPR) absorption peaks at 410 nm and 510 nm. Rhodamine S (RhS) cationic dye was absorbed on the as‐prepared AgNC substrate to obtain a RhS–AgNC surface‐enhanced Raman scattering (SERS) nanoprobe that exhibited a strong SERS peak at 1506 cm –1 and a strong RRS peak at 375 nm. Upon addition of the analyte sodium hexametaphosphate (HP), it reacted with RhS, which resulted in a decrease in the SERS and RRS peaks that was studied in detail. The decreased SERS and RRS intensities correlated linearly with HP concentration in the range of 0.0125–0.3 µmol/L and 0.05–1.0 µmol/L, with a detection limit of 6 nmol/L and 20 nmol/L HP respectively. Due to advantages of high sensitivity, good selectivity and simple operation, the RhS molecular probes were used to determine HP concentration in real samples. Copyright © 2015 John Wiley & Sons, Ltd.